QUERCETIN: A POTENTIAL NATURAL DRUG FOR ADJUVANT TREATMENT OF RHEUMATOID ARTHRITIS - Jun Ji, Jian; Lin, Yuan; Shan Huang, Shan; Li Zhang, Hou; Peng Diao, Yun; Li, Kun (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Rheumatoid arthritis (RA) is the rheumatism mainly manifested as disabling joint disease and mainly involves hands, wrists, feet and other small joints. Recurrent arthritis attacks, synovial cell hypertrophy and hyperplasia and bone and cartilage damages eventually lead to joint dysfunction and other complications, and there is no cure. Quercetin (QU) is a kind of natural flavonoids, with lipid-lowering, anti-inflammatory and other pharmacological activities, and minor toxic side effects. Thus, we assume that QU may be an adjuvant natural drug for treatment of RA. The possible mechanism is through regulation of NF-κB, to inhibit the transcription of joint synovitis factors, hinder the generation of inflammatory factors, and inhibit the inflammatory reaction; through inhibiting the activities of VEGF, bFGF, MMP-2 and other cytokines, to inhibit angiogenesis in multiple links and inhibit synovial pannus formation. QU may be an adjuvant natural drug for treatment of RA.